2020
DOI: 10.1055/s-0040-1710072
|View full text |Cite
|
Sign up to set email alerts
|

Influência da superfície dos parafusos pediculares no torque de inserção e resistência ao arrancamento

Abstract: Resumo Objetivo Comparar por testes mecânicos a resistência ao arrancamento e o torque de inserção do parafuso pedicularjateado e liso. Métodos Parafusos pediculares de superfície áspera e de superfície lisa com diâmetros de 4,8; 5,5 e 6,5 mm foram inseridos em blocos de poliuretano com densidade de 10 PCF (0,16 g/cm3). O torque de inserção e a força de arrancamento foram avaliados. Resultados A força de arrancamento dos parafusos de superfície áspera e de superfície lisa não dife… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 14 publications
0
1
0
Order By: Relevance
“…In the bilateral screw-rod system, reinsertion also has no significant effect on pullout strength 35 . A new research suggested that the roughness of surface is another important factor for insertion torque 36 . Incidence of screw breakage ranges between 2.6 and 60% 8 10 and its occurrence represents a serious problem.…”
Section: Discussionmentioning
confidence: 99%
“…In the bilateral screw-rod system, reinsertion also has no significant effect on pullout strength 35 . A new research suggested that the roughness of surface is another important factor for insertion torque 36 . Incidence of screw breakage ranges between 2.6 and 60% 8 10 and its occurrence represents a serious problem.…”
Section: Discussionmentioning
confidence: 99%